The direct medical cost of type 2 diabetes mellitus in South Africa: a cost of illness study. Issue 1 (1st January 2019) - Erzse, Agnes; Stacey, Nicholas; Chola, Lumbwe; Tugendhaft, Aviva; Freeman, Melvyn; Hofman, Karen
ABSTRACT: Background : Type 2 diabetes mellitus (T2DM) is known to require continuous clinical care and management that consumes significant health-care resources. These costs are not well understood, particularly in low- and middle-income countries. Objective : The aim of this study was to estimate the direct medical costs associated with T2DM in the South African public health sector and to project an estimate of the future direct costs of T2DM by 2030. Methods : A cost of illness study was conducted to estimate the direct medical costs of T2DM in South Africa in 2018 and to make projections for potential costs in 2030. Costs were estimated for diagnosis and management of T2DM, and related complications. Analyses were implemented in Microsoft Excel, with sensitivity analysis conducted on particular parameters. Results : In 2018, public sector costs of diagnosed T2DM patients were approximately ZAR 2.7 bn and ZAR 21.8 bn if both diagnosed and undiagnosed patients are considered. In real terms, the 2030 cost of all T2DM cases is estimated to be ZAR 35.1 bn. Approximately 51% of these estimated costs for 2030 are attributable to the management of T2DM, and 49% are attributable to complications. Conclusion : T2DM imposes a significant financial burden on the public healthcare system in South Africa. Treatment of all prevalent cases would incur a cost equivalent to approximately 12% of the total national health budget in 2018. With rising prevalence, direct costs will grow if current care regimes are maintained and case-finding improved. Increased financial resources are necessary in order to deliver effective services to people with T2DM.